2016
DOI: 10.1155/2016/9186232
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Intestinal Flora of Uygur and Han Ethnic Chinese Patients with Ulcerative Colitis

Abstract: Aim. To study the correlation between intestinal flora and ulcerative colitis by analyzing the abundance of Bacteroides, Fusobacterium, Clostridium, Bifidobacterium spp., and Faecalibacterium prausnitzii in the intestinal of ulcerative colitis (UC) patients and healthy controls with Uygur and Han ethnic. Methods. Bacterial genomic DNA was extracted from fecal samples and analyzed with real-time fluorescence quantitative polymerase chain reaction (PCR) to identify the abundance of Bacteroides, Fusobacterium, Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Several studies have used high-throughput techniques to study the mucosa-associated microbiota in IBD and IBS patients ( 54 , 55 ). Interestingly, there is still no consensus on the changes in Bacteroides abundance in colonic mucosal tissues of intestinal-related diseases ( 56 58 ). However, we believe that the decrease of Bacteroides on the mucosal layer due to a HFD may be involved in the perturbation of intestinal mucosal barrier, thereby promoting the occurrence of IBD or CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used high-throughput techniques to study the mucosa-associated microbiota in IBD and IBS patients ( 54 , 55 ). Interestingly, there is still no consensus on the changes in Bacteroides abundance in colonic mucosal tissues of intestinal-related diseases ( 56 58 ). However, we believe that the decrease of Bacteroides on the mucosal layer due to a HFD may be involved in the perturbation of intestinal mucosal barrier, thereby promoting the occurrence of IBD or CRC.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, F. prausnitzii has been demonstrated to involve in the maintenance of intestinal health ( 26 , 29 46 ). Of note, some studies have shown that there is a significant difference in F. prausnitzii between healthy people and UC patients ( 30 , 31 , 33 38 , 41 , 46 ). Compared with healthy people, F. prausnitzii species had lower counts in UC patients ( 30 35 , 38 , 40 44 ).…”
Section: Part I: Microbiotamentioning
confidence: 99%
“…Of note, some studies have shown that there is a significant difference in F. prausnitzii between healthy people and UC patients ( 30 , 31 , 33 38 , 41 , 46 ). Compared with healthy people, F. prausnitzii species had lower counts in UC patients ( 30 35 , 38 , 40 44 ). For instance, Machiels et al introduced real-time PCR analysis to find that F. prausnitzii in UC patients had a lower abundance than health people.…”
Section: Part I: Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of UC is mainly anti-inflammation and immune response regulation [6]. In recent years, studies have found that severe intestinal flora imbalances are closely related to the occurrence of UC, so the research and application of microecological agents are getting more and more attention [7–9]. Accumulating evidences have suggested that intestinal microbiota plays an important role in the pathogenesis of this disorder [10,11].…”
Section: Introductionmentioning
confidence: 99%